CO-CREATION AND THE CREATIVE ECONOMY : REDEFINING PUBLIC SERVICE DELIVERY FOR INCLUSIVE INNOVATION - Dessy Ruhati; Triyuni Soemartono; Khasan Effendy; T. Herry Rachmatsyah (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The creative economy has emerged as a dynamic engine of economic resilience and social innovation, especially in the aftermath of the COVID-19 pandemic. This article explores the interaction between co-creation and creative economic ecosystems, emphasizing how participatory governance models can enhance public service delivery and foster inclusive development. Drawing on mixed-methods research involving 450 creative enterprises and over 100 stakeholder interviews across Indonesia, Portugal, and Spain, the study investigates the enabling conditions for co-creation, namely digital literacy, institutional flexibility, and stakeholder engagement. Quantitative analysis using structural equation modeling highlights the mediating role of digital skills in enhancing business sustainability, while qualitative insights reveal barriers such as bureaucratic inertia and algorithmic governance. Case studies of creative kampongs in Bandung, innovation labs in Gipuzkoa, and hybrid tourism platforms in Lisbon demonstrate the transformative potential of collaborative service design. However, the research also cautions against superficial participation, showing that power asymmetries can undermine co-creation outcomes without institutional safeguards. The findings demonstrate the need for adaptive governance structures, integrated cultural impact indicators, and platform reforms to ensure equitable participation. This study promotes a paradigm shift towards relational and iterative governance that values local knowledge, encourages experimentation, and propels sustainable growth by integrating creative economy principles into public policy frameworks. This article contributes to contemporary debates on public innovation by proposing a co-creation framework grounded in cultural vitality, digital empowerment, and democratic inclusivity. Keywords: Creative Economy; Co-creation; Public Service Innovation; Governance